2017
DOI: 10.1039/c6se00023a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of La2O3composition in MgO–La2O3mixed oxide-supported Co catalysts on the hydrogen yield in glycerol steam reforming

Abstract: Partially Mg-substituted LaCoO3perovskite is a good precursor, for the generation of cobalt nanoparticle derived under the reduction atmosphere. The La2O2CO3phase formed is more efficient in removing the carbon from the cobalt active site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Figure S2). Similar behavior was reported by Surendar and colleagues 44 when Mg 2+ was partially inserted into La 3+ , which resulted in a shift of La 2 O 3 XRD peaks. They also reported the enhancement of metal dispersion and the high reducibility as a result of the interaction between La and MgO.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 86%
“…Figure S2). Similar behavior was reported by Surendar and colleagues 44 when Mg 2+ was partially inserted into La 3+ , which resulted in a shift of La 2 O 3 XRD peaks. They also reported the enhancement of metal dispersion and the high reducibility as a result of the interaction between La and MgO.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 86%
“…Subsequently, reaction of R5 occurred due to the presence of char in the support, and CO was produced that could reduce compound Ni to elemental Ni. Meanwhile, the higher the La content, the broader and weaker were the characteristic peaks of NiAl2O4 that appeared, demonstrating that the crystal particles became smaller (Surendar et al 2017). This result revealed that La could effectively decrease the particle size of NiAl2O4.…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 89%
“…[45] Prasad et al utilized MgO-La 2 O 3 supported Co catalyst for complete conversion of glycerol at 700 °C. [46] Although, the glycerol reforming process led to the production of H 2 gas, but it suffers from the cumbersome postproduction purification of H 2 gas, due to the contamination of CO, CO 2 , CH 4 . Alternatively, H 2 gas can be produced from oxidant-free [47,48] or O 2 free [49] dehydrogenation of glycerol to lactic acid.…”
Section: Introductionmentioning
confidence: 99%